2021
DOI: 10.3390/biomimetics6030042
|View full text |Cite
|
Sign up to set email alerts
|

Self-Actuated Paper and Wood Models: Low-Cost Handcrafted Biomimetic Compliant Systems for Research and Teaching

Abstract: The abstraction and implementation of plant movement principles into biomimetic compliant systems are of increasing interest for technical applications, e.g., in architecture, medicine, and soft robotics. Within the respective research and development approaches, advanced methods such as 4D printing or 3D-braiding pultrusion are typically used to generate proof-of-concept demonstrators at the laboratory or demonstrator scale. However, such techniques are generally time-consuming, complicated, and cost-intensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 47 publications
(69 reference statements)
0
15
0
Order By: Relevance
“…[ 489,532,533,558 ] Other recent work has demonstrated low‐cost, wood‐ and paper‐based hygroscopic actuators for use in educational settings to teach more intuitively about soft robotics and botany. [ 559 ] Another notable publication details a modular fluidic engine for soft actuators. [ 560 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 489,532,533,558 ] Other recent work has demonstrated low‐cost, wood‐ and paper‐based hygroscopic actuators for use in educational settings to teach more intuitively about soft robotics and botany. [ 559 ] Another notable publication details a modular fluidic engine for soft actuators. [ 560 ]…”
Section: Resultsmentioning
confidence: 99%
“…[489,532,533,558] Other recent work has demonstrated low-cost, wood-and paper-based hygroscopic actuators for use in educational settings to teach more intuitively about soft robotics and botany. [559] Another notable publication details a modular fluidic engine for soft actuators. [560] While the fluidic medium seems to be representative of the field, the electrical medium is the most commonly utilized overall.…”
Section: Function Mediamentioning
confidence: 99%
“…Poppinga et al [8] show that a variety of complex plant movement principles can be demonstrated with comparably simple handcrafted compliant systems based on paper, wood, plastic foil and/or glue as construction materials. The handcrafted systems are selfactuated by shrinking processes triggered by the anisotropic hygroscopic properties of the wood or paper.…”
Section: Broad Spectrum Of Topicsmentioning
confidence: 99%
“…In this context, paper materials offer a variety of benefits as they are fully recyclable and originate from biogenic polymeric resources. Due to its nature, paper can be used as a versatile platform for a variety of applications, such as microfluidic devices like lateral flow assays for the rapid detection of different molecules in analytes [ 7 , 8 ], devices for sensing strain, gas, and humidity [ 9 , 10 ], and self-actuated devices that are driven by changes in temperature, light, or humidity [ 11 , 12 ]. Most of these soft robotic devices are fabricated by modifying the paper with, e.g., stimuli-responsive polymers, small molecules, or inorganic particles in order to achieve the desired properties [ 13 ].…”
Section: Introductionmentioning
confidence: 99%